2021
DOI: 10.1111/ijcp.14091
|View full text |Cite
|
Sign up to set email alerts
|

Female awareness about the preconception use of folic acid supplements in childbearing age: A cross‐sectional study

Abstract: Aims Folic acid is required for the growth and development of the fetus. There is strong evidence that taking folic acid before pregnancy and during the first trimester reduces the risk of neural tube defects (NTDs). This study aimed to assess women's awareness of preconception folic acid supplementation and its importance to the mother and the fetus. Methods This was a cross‐sectional questionnaire study conducted in Saudi Arabia between January and April 2019. An electronic questionnaire tool was designed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
2
8
0
1
Order By: Relevance
“…This study aimed to investigate the knowledge and awareness of FA and FA supplementation of a cohort of undergraduate female students, and determine the possible predictors for knowledge of FA and FA supplementation. In this study, we found that 61.0% of our respondents were aware and have knowledge of FA similar to the findings conducted in Korea and many other countries [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. However, our study population were college students compared to other studies where the respondents were general populations of women.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This study aimed to investigate the knowledge and awareness of FA and FA supplementation of a cohort of undergraduate female students, and determine the possible predictors for knowledge of FA and FA supplementation. In this study, we found that 61.0% of our respondents were aware and have knowledge of FA similar to the findings conducted in Korea and many other countries [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. However, our study population were college students compared to other studies where the respondents were general populations of women.…”
Section: Discussionsupporting
confidence: 87%
“…A survey conducted in Korea showed that 65.6% of surveyed women had heard of FA before pregnancy, and 26.4% reported on the pre-conceptional use of FA [ 9 ]. 9 In some other studies, the knowledge regarding FA need varied from 34.0% to over 67% [ 10 , 11 , 12 , 13 , 14 , 15 ]. However, despite their knowledge, few women, as low as 9.4% in some studies to as much as 46.3% in others, in their childbearing age take FA supplements [ 11 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to limitations in economic development level, local food varieties, and culinary habits, developing countries are at a higher risk of folate de ciency and its adverse effects [6]. With increasing physiological folate need for procreation, folate de ciency often appears in women of childbearing age [7]. Folate de ciency could affect health, lead to severe consequences for future generations, and bring further substantial economic and social losses [8].…”
Section: Introductionmentioning
confidence: 99%